Vocabulary Learning Strategies, Linguistic Knowledge and Reading Comprehension Among Graduating Senior Students - Almirol, Mary Rose (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the vocabulary learning strategies, dictionary-level linguistic knowledge, and reading comprehension of Grade 12 students at Palandok National High School, District of Bacungan, Leon B. Postigo, Zamboanga del Norte. Anchored on vocabulary learning strategy taxonomy, the Vocabulary Levels Test framework, and constructivist views of reading comprehension, the study employed a quantitative-descriptive research design. Total enumeration was used, involving 95 Grade 12 students composed of 49 Humanities and Social Sciences students and 46 Home Economics students specializing in Cookery, Bread, and Pastry Production. Data were gathered using an adopted vocabulary learning strategies questionnaire, the updated Vocabulary Levels Test, and an adopted 45-item reading comprehension test. Findings showed that students often used vocabulary learning strategies, with social strategies obtaining the highest mean and cognitive strategies obtaining the lowest. The students demonstrated stronger performance in high-frequency vocabulary levels but showed increasing difficulty as vocabulary levels became more advanced. All respondents were classified under the frustration level in reading comprehension, indicating a serious comprehension gap. The study concluded that vocabulary learning strategies remain important in improving linguistic knowledge and reading comprehension, especially when students are given sustained exposure to English words and academic reading materials. It recommended the use of a complete system of vocabulary learning strategies, outcomes-based vocabulary activities, and further inferential studies on the relationships among vocabulary learning strategies, linguistic knowledge, and reading comprehension. The study supports SDG 4, SDG 8, and SDG 10 by promoting quality education, employability-related language competence, and inclusive support for learners in rural contexts. Its sustainability impact lies in strengthening educational and socio-economic readiness through practical, classroom-based language interventions.
Keywords: Academic Reading Materials; Dictionary-Level Linguistic Knowledge; Grade 12 Students; Reading Comprehension; Senior High School; Vocabulary Learning Strategies; Vocabulary Levels Test